Evolution of particle interactions between accidentally released aerosol particles generated from powdered engineered nanomaterials into a simulated workplace atmosphere. (March 2019) - Kylafis, Georgios F.; Tomlin, Alison S.; Sleigh, P. Andrew; Vignes, Alexis
Abstract: The evaluation of aerosol processes which alter the size distribution of accidentally released nanomaterial particles in an indoor environment can provide size resolved exposure estimations, and subsequently contribute to a more comprehensive risk analysis on engineered nanomaterials (ENMs). In this work processed suspensions of TiO2 and SiO2 nanopowders were introduced into the reservoir of a nebuliser, and injected continuously as nano-aerosols into a room-size dispersion facility for a fixed release time. Following injection, the concentration of the dispersed aerosols was allowed to naturally decay for a prolonged period. Airborne particle number concentration (PNC) and particle size distributions (PSD) were continuously measured at a point within the breathing zone near to the source, while deposited particles were collected for transmission electron microscopy (TEM) analysis. A log10 -normal fitting program was used to determine the evolution of the modal groups present within the measured PSDs. A modelling approach that considered the experimentally determined particle decay rate as a sum of the pair to pair coagulation and deposition rates was employed to estimate the relative importance of size-resolved deposition compared to coagulation. Results indicated that the variation of PNC with time was accurately modelled, providing size-dependent insights into the contribution of the two particle removal mechanisms to the change of PNC over time. The deposition patterns obtained from the TEM images qualitatively supported the model results. Since a limited set of input parameters were used, we concluded that the proposed model could be an effective tool for a reasonable quantification of worker's exposure to aerosols originating from the accidental release of diffuse ENM in real workplaces. Highlights: Dispersion experiments with engineered nanomaterials in an enclosed chamber. Quantification of coagulation and deposition through a particle process model. The changes in size-resolved PNC over time were accurately modelled. The TEM images qualitatively supported the model results.